PEMBARUAN UI/UX ZALORA UNTUK PENINGKATAN PENGALAMAN MARKETPLACE SELLER & CUSTOMER - Susi Hartanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
To improve the shopping experience for customers, and provide better selling experience services for marketplace sellers, as of 2021-2022, Zalora updated the UI/UX on the Zalora platform and seller center. There are 8 additional features that are considered to help sellers and customers interact better: 1) Seller Rating Information; 2) There are new payment methods, especially pay later; 3) Payment method improvement; 4) Account verification via email and cellphone number; 5) Address input via geocoding; 6) Voucher in PDV; 7) Zalora Interactive Store; 8) Loyalty Programs; and 9) Z-Live. Key words : UI, UX, Zalora, Marketplace, Seller, Customer Untuk meningkatkan pengalaman berbelanja bagi pelanggan, dan memberikan servis pengalaman berjualan yang lebih baik bagi penjual marketplace, per 2021-2022, Zalora memperbarui UI/UX pada platform Zalora dan seller center. Adapun 8 fitur tambahan yang dinilai membantu para penjual dan pelanggan berinteraksi lebih baik: 1) Informasi Rating Penjual; 2) Ada metode pembayaran baru, terutama paylater; 3) Perbaikan Metode Pembayaran; 4) Verifikasi akun via email dan nomor hp; 5) Input alamat melalui geokoding; 6) Voucher in PDV; 7) Zalora Interactive Store; 8) Program Loyalti; dan 9) Z-Live. Kata Kunci: UI, UX, Zalora, Marketplace, penjual, pelanggan